Application of Gold Nanoparticles in Colorimetric Detection - Duenchay, Paweenar (Journal of Advanced Development in Engineering and Science, 2023)
Nowadays, Nano-Material have been widely developed and applied in engineering, medical, environment, catalyst and chemical analysis. Gold nanoparticles are the stable metal particles which show ability of unique color properties. Gold nanoparticles can change the color according to the size or shape of the particles. With this feature, it is popular to be applied in the field of colorimetric detection. Moereover, the application of gold nanoparticles in colorimetric detection can be used to measure biological substances in the body and determine the amount of metal in the environment. These applications can be analyzed simply and rapidly without requiring complicated instruments. In the future, it can also be developed into a portable measuring device that can perform measurements in the field analysis.